Strategies to Improve Budget Absorption at the Secretariat of the National Human Rights Commission of Papua Province - Christine Maisye Mansawan; Neneng Sri Rahayu; Edy Sutrisno (Yayasan Riset dan Pengembangan Intelektual, 2023)
The low budget absorption at the Papua Provincial Secretariat is caused by the lack of implementation of the reimbursement of supplies (Reloving) so that it experiences a buildup and results in absorption at the end of the year the purpose of this study is to optimize the factors that support budget absorption, namely budget planning factors, budget execution, administrative recording, human resource competencies and organizational commitment, in addition to knowing the strategy in increasing budget absorption, research conducted at the office of the National Human Rights Commission of the Papua Provincial Secretariat by using Qualitative research methods by conducting interviews with 3 (three) respondents. The results of this research show that budget planning factors, budget execution, administrative recording, human resource competence are factors that support the budget absorption process. The strategy in increasing budget absorption is to develop standard operation procedures related to the workflow of financial management at the Papuan representative secretariat, submit a memorandum of service from the National Commission of the Papuan representative secretariat regarding budget allocation by taking into account the level of cost and the number of employees at the Papuan representative secretariat, besides making routine and quarterly monitoring and evaluation reports.